Pemberdayaan Petani Pemula melalui Pelatihan Teknik Penyadapan Karet yang Optimal - Tina Endriani; Dandi Saputra; Farhan Moreno Akbar; Santi Fitri; Dora Fatma Nurshanti (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
Sinar Bhakti Village, located in Ogan Komering Ulu Regency, holds significant potential in rubber plantation management. However, suboptimal rubber tapping techniques often pose a major challenge for beginner farmers, resulting in low production yields and damage to rubber trees. This community service program aims to empower beginner farmers through training on optimal rubber tapping techniques. The method used was a participatory approach with hands-on field training. The training was conducted on Saturday, January 19, 2025, and included the introduction of tapping tools, proper tapping techniques, and post-tapping tree care. The activity involved beginner farmers in Sinar Bhakti Village. The results indicate that the training successfully enhanced participants' understanding of proper rubber tapping techniques. All participants effectively applied the techniques during field simulations. Additionally, participants demonstrated increased confidence in managing rubber plantations independently. This program positively impacted not only rubber productivity but also the economic sustainability of the village community.